Spatio-temporal patterns of pressure over the North Atlantic - Antunes, Sílvia (2020)
The North Atlantic mean sea level pressure ﬁeld variability is analysed. A space–time study is performed using multichannel singular spectral analysis, allowing the detection of signiﬁcant space–time modes of variability with periodicity behaviour. It is shown that there is a space variability associated with the time variability of the pressure ﬁeld. The oscillation is not quasi-meridional but has different orientations, rotating in a cycle, with a periodicity of about 9 years, from the positive North Atlantic oscillation (NAO) phase through the negative NAO phase and again to the positive phase. This periodicity behaviour was previously detected in the temporal principal components extracted from a principal component analysis but, in the time domain, it was found as not signiﬁcant. Furthermore, the analysis of a long series of an NAO index had already revealed similar periodicity behaviour.